Glaucoma following cataract surgery in the first 2 years of life: frequency, risk factors and outcomes from IoLunder2. Issue 7 (5th October 2019) - Solebo, Ameenat Lola; Rahi, Jugnoo S
Abstract : Background: We investigated glaucoma related adverse events, predictors and impact at 5 years following surgery in the IoLunder2 cohort Methods: Population based observational cohort study of children undergoing cataract surgery aged 2 years or under between January 2009 and December 2010. Glaucoma was defined using internationally accepted taxonomies based on the consequences of elevated intraocular pressure (IOP). Glaucoma related adverse events were any involving elevated IOP. Multivariable analysis was undertaken to investigate potential predictors of secondary glaucoma with adjustment for within-child correlation in bilateral cataract. Unilateral and bilateral cataract were analysed separately. Results: Complete follow-up data were available for 235 of 254, 93% of the inception cohort. By 5 years after primary cataract surgery, 20% of children with bilateral cataract and 12% with unilateral had developed secondary glaucoma. Glaucoma related complications had been diagnosed in 24% and 36% of children, respectively. Independent predictors of glaucoma were younger age at surgery (adjusted OR for reduction of week in age: 1.1, 95%C I 1.1 to 1.2, p<0.001); the presence of significant ocular comorbidity (adj OR 3.2, 95% CI 1.1 to 9.6, p=0.01); and shorter axial length (adj OR for each mm 1.7, 95% CI 10.0 to 1, p=0.05) for bilateral cataract. Shorter axial length was the single independent factor in unilateral disease (adj OR 9.6, 95% CI 1.7 to 52, p=0.009) Conclusions: Both younger age at surgery (the strongest marker of ocular 'immaturity') and smaller ocular size (a marker of both immaturity and developmental vulnerability) can be used to identify those at greatest risk of glaucoma due to early life cataract surgery.